Prevalence and Identification of Carbofuran Degrading Bacteria from Agricultural Fields and Associated Water Bodies - Hossain, Anamica; Rahman, Reazur; Jahan, Nusrat; Akhter, Humaira; Begum, Anowara (Bangladesh Journal of Microbiology, 2023)
The extensive use of pesticides in agricultural areas is done to assure protection against insect invasion, to raise crop production, to improve fertility and soil quality, and therefore to efficiently contribute to an agriculture-based economy. However, the unfortunate reality is that the long-term presence of these pesticides in the environment as a result of their complex and xenobiotic chemical structures leads to bioaccumulation as well as bio-magnification, which in turn causes toxicity, chronic disabilities, hormonal imbalance, reproductive and endocrine dysfunctionalities, and many other health issues in humans as well as other vertebrates and causes ecosystem derangement. Similar results are produced by one of the most widely used N-methylcarbamate-based pesticides, carbofuran. There is no better solution to this issue than breakdown of leftover pesticide in the environment to harmless, native components through biological agents, ideally indigenous bacteria. Carbofuran, one of the most widely used N-methylcarbamate-based insecticides, has comparable effects. In light of this, a study was conducted to identify and characterize bacteria that have the innate ability to not only survive pesticide applications to rice and vegetable fields, but also to use the pesticides as a source of energy and break them down into harmless, environmentally friendly components. As a result, samples were taken from a Savar rice and tomato field shortly after a pesticide application, and Carbofuran 5G was the insecticide selected to check for degradability given to its widespread use there. Bushnell Haas broth and Bushnell Haas agar media were employed for enrichment, plating, and subsequent cultures to generate pure culture, with supplemented carbofuran of different concentrations serving as the only carbon source. The identities of the 17 isolates that could grow there were verified by sequencing after PCR and product purification. The evolutionary relatedness was determined using phylogenetic analysis with MEGAX. Acinetobacter spp., Rahnella spp., Chitinophaga spp., Serratia spp., Stenotrophomonas spp., Achromobacter spp., Pseudoxanthomonas spp., and Klebsiella spp. were the bacteria that were found. Bangladesh J Microbiol, Volume 39, Number 2, December 2022, pp 68-74